Trouting on the Brulé River, or, Lawyers' summer-wayfaring in the northern wilderness - King, John Lyle. (Lawyers' summer-wayfaring in the northern wilderness, 1879)
Trouting on the Brule River is a literary account of genteel sportsmen's fishing expeditions during the summers of 1875 and 1877. Originally published in the Chicago Sunday Times and the Chicago Sunday Tribune, the book's chapters tell how a group of Chicago lawyers traveled by rail, foot and canoe to destinations along the Menominee, Michigami, and Brule Rivers in Michigan's Upper Peninsula. The author describes the delights of fly-fishing in lyrical detail, along with bobbing for pike, shooting rapids, deer and duck hunting, and encounters with birds and animals. He romanticizes the expedition's Indian guides, believing that they lived in a state of nature.
Trouting on the Brule River is a literary account of genteel sportsmen's fishing expeditions during the summers of 1875 and 1877. Originally published in the Chicago Sunday Times and the Chicago Sunday Tribune, the book's chapters tell how a group of Chicago lawyers traveled by rail, foot and canoe to destinations along the Menominee, Michigami, and Brule Rivers in Michigan's Upper Peninsula. The author describes the delights of fly-fishing in lyrical detail, along with bobbing for pike, shooting rapids, deer and duck hunting, and encounters with birds and animals. He romanticizes the expedition's Indian guides, believing that they lived in a state of nature.
Also available in digital form on the Library of Congress Web site.
Keywords: Trout fishing / Michigan.; Brule River (Mich. and Wis.); Upper Peninsula (Mich.) / Description and travel.